Knowledge, attitude and practice of breakfast consumption among health sciences and non-health sciences students of International Islamic University Malaysia (IIUM) - Zahri, Siti Zalifah; Azahari, Nuraniza (IIUM Press, International Islamic University Malaysia, 2024)
Background: Regular breakfast consumption is recommended as part of a healthy lifestyle, as it helps individuals meet their nutritional needs and benefits their mental health, emotional well-being, and positive social interactions. However, the prevalence of breakfast consumption remains low among university students. Therefore, this study aims to assess the levels of knowledge, attitude, and practice (KAP) regarding breakfast consumption among health sciences and non-health sciences students at the International Islamic University Malaysia (IIUM). Methods: A convenience sampling method was used to recruit 382 on-campus undergraduate participants , with 191 health sciences students from the Kuantan campus and 191 non-health sciences students from the Kuantan, Gombak, and Pagoh campuses. An online questionnaire was distributed, comprising four sections: sociodemographic information, knowledge, attitude, and practice related to breakfast consumption. Results: The results showed that while 66% of IIUM students had a high level of knowledge about the breakfast consumption, 92% had only moderate attitudes towards it, and 84% displayed moderate breakfast practice. Health sciences students exhibited significantly higher knowledge levels compared to non-health sciences students. No significant differences were found between knowledge and practice. Notably, significant associations were identified between knowledge and attitude, and between attitude and practice concerning breakfast consumption. Conclusion: These findings indicate a need for universities to implement educational programs and interventions to promote regular breakfast consumption and healthier eating patterns among students.